Scandinavian Arrowheads of the Viking Age, Their Manufacture and Distribution - Hector Cole (EXARC Journal, 2023)
In recent years there has been a renewed interest in the arrowheads used in the Viking Age and their distribution. The 187 excavation of Viking graves in the Black Earth of Birka region of Sweden, re-examined in 2019 by Price (Price, et al., 2019) and the finding of arrows and arrowheads where glaciers have melted in Norway, prompted my research into the forging techniques of specific arrowheads from these finds, along with Viking arrowheads found in settlements in Ireland.